The Influence Of Health Education And Counseling On The Level Of Adolescents Knowledge About Reproductive Health In Rejomulyo Village, Kediri City - Joko Sutrisno; Maya Sopiana (Journal of Health Science Community, 2026)
Reproductive health issues remain a significant concern among adolescents. Data from the Indonesian Demographic and Health Survey (IDHS) in 2012 indicate an increase in premarital sexual behavior among adolescents, which may lead to various negative consequences such as unwanted pregnancy, abortion, sexually transmitted infections, and sexual violence. This condition highlights the importance of health education efforts to improve adolescents’ knowledge of reproductive health. This study aimed to determine the effect of health education counseling on adolescents’ knowledge of reproductive health. This study employed a quasi-experimental design using a one group pre-test and post-test approach. A total of 20 respondents were selected using purposive sampling. Data were collected using a reproductive health knowledge questionnaire. Health education counseling was provided after the pre-test, followed by a post-test to assess changes in knowledge levels. Data analysis was conducted using the paired sample t-test. The results showed an increase in adolescents’ knowledge levels after receiving health education counseling. Statistical analysis revealed a significant difference between knowledge levels before and after the intervention (p = 0.036). Conclusion Health education counseling has a significant effect on improving adolescents’ knowledge of reproductive health